2019
DOI: 10.1109/access.2019.2900303
|View full text |Cite
|
Sign up to set email alerts
|

Using Micro-Doppler Radar to Measure Gait Features Associated With Cognitive Functions in Elderly Adults

Abstract: This paper used micro-Doppler radar (MDR) measurements to investigate the significance of associations between cognitive functions and gait features of elderly persons. The aim of this paper was to develop a system that would enable the risks of developing dementia and related diseases to be monitored remotely on a daily basis. Study participants were adults aged 75 years and older. Gait velocity parameters corresponding to the walking speed and leg and foot velocities were remotely extracted via a simple 24-G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 40 publications
1
34
0
Order By: Relevance
“…The reason for MCI screening capability using the extracted gait parameters is that the gait dysfunction due to cognitive decline was detectable even though the decline is mild. In our previous study [6], the participants with larger cognitive declines in various cognitive domains were classified with the radar gait parameters. Although the MCI corresponds to a milder cognitive decline compared to our previous study, Ref.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The reason for MCI screening capability using the extracted gait parameters is that the gait dysfunction due to cognitive decline was detectable even though the decline is mild. In our previous study [6], the participants with larger cognitive declines in various cognitive domains were classified with the radar gait parameters. Although the MCI corresponds to a milder cognitive decline compared to our previous study, Ref.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the MCI screening was achieved using the gait parameters. However, the parameters extracted from V u ðtÞ were not selected for the logistic regression model despite our previous findings [6] of the efficacy of these parameters in leg forward motion for the evaluation of various cognitive functions. The mechanism of our results including the reason for the ineffectiveness of V u ðtÞ could be investigated using a larger dataset in future studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent researches are then focused on advancements and developments of UWB systems for their advantages and feasibility for monitoring gait and fall parameters. The authors in [ 32 ] suggested a relation between cognitive functions in the elderly and the gait velocity measured by a micro-Doppler radar. The use of an UWB technology to detect falls in domestic environments is presented in [ 33 ].…”
Section: Introductionmentioning
confidence: 99%